Pengaruh Kepemilikan Manajerial, Dewan Komisaris Dan Komite Audit Terhadap Kinerja Prusahaan Sektor Pertambangan Di Bursa Efek Indonesia - Ariful Fikri; Mukhlizul Hamdi (Fakultas Ekonomi dan Bisnis Universitas Bung Hatta, 2021)
This study aims to determine the impact of managerial ownerships, board of commissioners and audit committee on the achievement of mining sector companies in the Indonesia Stock Exchange. The sample used is the mining sub-sector company. Data used from 2015 to 2019. The hypothesis testing process is carried out with multiple regression partial testing. The results of testing the first hypothesis found that managerial ownership had no significant effect on company performance, while the board of commissioners and audit committee had a significant effect on the performance of the coal mining sub-sector companies on the Indonesia Stock Exchange. Keywords: Return on Assets, Good Corporate Governance & Mining Sub Sector